The unexpected effect of social status on reproduction: a case study in Joseon Korea from the nineteenth to the twentieth centuries - Lee, Sangkuk; Yoo, Jane (History of the Family, 2018)
We examine how parents have made decisions about the number of children they have, given their social status in accordance with residential location (either urban or rural areas) and time (either the pre-modern or modern periods). We use two sets of microdata–Jokbo and Jejeokbu–spanning the early nineteenth to mid-twentieth centuries in Korea. Combining the two data-sets, we use multiple imputation to fill the missing entries of some observations and apply a Poisson regression model on the augmented data. Our empirical results reveal statistically significant evidence that higher socioeconomic status is related to having more children. Additionally, our findings indicate that: (1) all else being constant, among high-status people, rural residents had more children than urban families; (2) for people born between 1800 and 1945, those born closer to the 1940s tended to have fewer children; and (3) during modernization, there was still a significant trend for high-status families to have more children.
Keywords: Jejeokbu; Jokbo; multiple imputation; Poisson regression; reproduction; Socioeconomic status